On the horns of a dilemma: experts as communicators for property‐level flood risk adaptation measures - Davids, Peter R.; Priest, Sally; Hartmann, Thomas (Technische Universität Dortmund, 2023)
This paper investigates the role of flood risk experts in supporting homeowners to implement property-level flood risk adaption (PLFRA). Homeowners can reduce their flood risks by implementing PLFRA. However, oftentimes they need advice on what sort of and how to implement PLFRA. This means that tailored experts advice is necessary to inform homeowners on such measures. But experience shows that mere information is often insufficient to motivate homeowners to realise measures. This contribution explores the reasons for the ineffectiveness of expert advice by investigating how expert advice responds to homeowners' rationalities. Based on a case study from Flanders, Belgium, this paper reveals how the relation between experts and homeowners differs related to different rationalities of homeowners. The paper uses Cultural Theory to discuss strategies on how experts, providing advice on property-level risk adaption, could move beyond engineering skills by also using risk communication skills in order to involve homeowners in flood risk governance.
Journal of flood risk management;16(2)
Keywords: Belgium; cultural theory; flood risk communication; flood risk experts; homeowners; property-level risk adaption; 710